2(1/4x-1)=2/3x+6

Simple and best practice solution for 2(1/4x-1)=2/3x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(1/4x-1)=2/3x+6 equation:



2(1/4x-1)=2/3x+6
We move all terms to the left:
2(1/4x-1)-(2/3x+6)=0
Domain of the equation: 4x-1)!=0
x∈R
Domain of the equation: 3x+6)!=0
x∈R
We multiply parentheses
2x-(2/3x+6)-2=0
We get rid of parentheses
2x-2/3x-6-2=0
We multiply all the terms by the denominator
2x*3x-6*3x-2*3x-2=0
Wy multiply elements
6x^2-18x-6x-2=0
We add all the numbers together, and all the variables
6x^2-24x-2=0
a = 6; b = -24; c = -2;
Δ = b2-4ac
Δ = -242-4·6·(-2)
Δ = 624
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{624}=\sqrt{16*39}=\sqrt{16}*\sqrt{39}=4\sqrt{39}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-24)-4\sqrt{39}}{2*6}=\frac{24-4\sqrt{39}}{12} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-24)+4\sqrt{39}}{2*6}=\frac{24+4\sqrt{39}}{12} $

See similar equations:

| 5(2n+8)=-90 | | 1/3(6x-3)=-11 | | 4=b-15 | | 55=3a+10 | | 50=–5h+70 | | 5x-3-11=2x+6-x | | 2x^2−8x−154=0 | | 18x-2+36x+2=76 | | x+4=23-x | | f-9=13 | | 2x-5+5-x+3x-2= | | 35x+2,000=6,375 | | 2w-13=49w= | | 2x-6=8+2 | | 7×z=70 | | 30x-10=80 | | .2/7(x–9)=–4 | | 2x-3=4(x+2 | | 3(2x-1)-11=-2x(3-x) | | 4r+5=-10r-9 | | 5+6y+6-4=6 | | 10=x+5+3 | | 20^x+9=55 | | 3x+4=7x-x-17 | | 6=t-15 | | 1/2(2p+8)=−p+5 | | 5t+14=19 | | 5=6y=6-4=6 | | 2(2x+9)=7x+6 | | 38.2=4x | | 12-r=2(r-4)-10 | | 14=d-8 |

Equations solver categories